2009
DOI: 10.1371/journal.pgen.1000332
|View full text |Cite
|
Sign up to set email alerts
|

A cis-Acting Diversification Activator Both Necessary and Sufficient for AID-Mediated Hypermutation

Abstract: Hypermutation of the immunoglobulin (Ig) genes requires Activation Induced cytidine Deaminase (AID) and transcription, but it remains unclear why other transcribed genes of B cells do not mutate. We describe a reporter transgene crippled by hypermutation when inserted into or near the Ig light chain (IgL) locus of the DT40 B cell line yet stably expressed when inserted into other chromosomal positions. Step-wise deletions of the IgL locus revealed that a sequence extending for 9.8 kilobases downstream of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
110
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(125 citation statements)
references
References 30 publications
14
110
1
Order By: Relevance
“…However, none of the known transcriptional control elements in mouse B cells appears to be absolutely required for SHM, suggesting a redundancy or unidentified elements (48). Recent studies discovered novel cis-acting elements in the IgL locus of the DT40 chicken B cell line that are both essential and sufficient for AIDmediated sequence diversification (59,60). In addition, it was shown that CAGGTG cis elements in the context of Ig enhancers were sufficient and essential to target mutations to a nearby transcribed gene in transgenic DT40 cell lines (61).…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the known transcriptional control elements in mouse B cells appears to be absolutely required for SHM, suggesting a redundancy or unidentified elements (48). Recent studies discovered novel cis-acting elements in the IgL locus of the DT40 chicken B cell line that are both essential and sufficient for AIDmediated sequence diversification (59,60). In addition, it was shown that CAGGTG cis elements in the context of Ig enhancers were sufficient and essential to target mutations to a nearby transcribed gene in transgenic DT40 cell lines (61).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, germline deletion of Ig enhancers has resulted in either normal SHM, or impaired SHM accompanied by reduced transcription. Interestingly, recent studies in the chicken DT40 B-cell line identified a large DNA region 3 0 of the Igl constant region with apparent SHM targeting activity [56,57].…”
Section: Box 1 the Targeting Of Shmmentioning
confidence: 99%
“…In the future, transgene diversification in DT40 may be accomplished by addition of gene conversion on top of hypermutation if homologous non-immunoglobulin conversion donor sequences are inserted upstream of the transgene, thus resembling the natural process of antibody diversity generation in avian species. Studies on AIDdependent gene diversification have revealed that natural restriction of hypermutation and gene conversion activities to the immunoglobulin loci is controlled by cis-regulatory sequences usually overlapping with immunoglobulin enhancers [62][63][64][65]. These findings pave the way to creation of non B cell hypermutating cell lines as platforms for directed protein evolution by means of modifying a cell line of interest.…”
Section: Eukaryotic In Vivo Evolution Systemsmentioning
confidence: 99%